Morphological integration of the cranium in Homo, Pan, and Hylobates and the evolution of hominoid facial structures. Issue 4 (30th December 2016) - Neaux, Dimitri
Abstract: Objectives: Modern humans diverge from other extant hominids (chimpanzees, gorillas, and orangutans) in a series of craniofacial morphological features. Like hylobatids, they possess a face with a reduced subnasal prognathism that is associated with a globular basicranium. These traits are not independent, as the skull is a complex integrated structure. The aim of the present study is to determine relationships between the face and the basicranium in two hominid genera ( Homo and Pan ) and a hylobatid genus ( Hylobates ) to test if these taxa share common patterns of integration linking these structures. Materials and Methods: Three dimensional (3D) geometric morphometric analyses and 3D homologous landmarks are used to compare the integration patterns between facial and basicranial structures in a comparative sample of Homo, Pan, and Hylobates . Pooled within‐genus partial least squares analyses are computed to describe and quantify these patterns of integration. Results: The covariation analyses show similar patterns of integration shared between the three studied taxa. These patterns correspond to the brachycephalic and dolichocephalic conditions previously defined in hominins and hominids. Discussion: Results confirm that hominoids share similar patterns of integration. This is in line with the hypothesis that morphological integration is mostly conservative in hominoids. These similar patterns of integration may explain the convergent evolution of short faces in humans and hylobatids.